Effect of reclaimed asphalt pavement on cracking performance of asphalt mixtures with regular and high polymer modified binders. Issue 7 (3rd July 2022) - Park, Bongsuk; Zou, Jian; Yan, Yu; Roque, Reynaldo; Lopp, George; Moseley, Howard
Abstract : Since reclaimed asphalt pavement (RAP) provides economic savings, incorporating RAP may reduce high cost of high-polymer (HP) binder typically used to address severe cracking. However, RAP is currently not allowed in HP mixtures in Florida, because aged RAP binder may reduce benefits of HP binder. This study focused on determining whether RAP can be used in HP mixtures, while maintaining the premium performance expected of HP binder. Eight RAP sources covering a broad range of RAP characteristics were assessed using the interstitial component fracture energy (FEIC ) and the mixture fracture energy (FEmix ). Mixtures with HP binder exhibited better cracking resistance than those with PG 76–22 binder. However, introduction of 20% RAP in HP mixtures reduced 20–60% in FEIC and 30–45% in FEmix, depending on RAP characteristics. Therefore, RAP characteristics need to be carefully reviewed, and more caution is needed when adding RAP into HP mixtures.